Germany: The Quest for World Class - Kehm, Barbara (International Higher Education, 2009)
In 2004 the education and research federal minister made a proposal to identify Germany's top-level institutions to secure Germany's competitiveness and economic future in the emerging knowledge society and to strengthen the international visibility of German universities as high-quality institutions with cutting-edge research. This plan formed the birth of the German "excellence initiative." The initiative not only triggered more competition among German universities; it also marked a conscious shift toward a more vertical differentiation of the system as a whole.